F.E. Analysis Of Fire Hazards From Metal Oxide Varistor Failures - Brugger, Richard D. (Journal of the National Academy of Forensic Engineers, 2000)
There Are Benefits In Using Metal Oxide Varistors (Mov, Movistors) In Electrical Circuits. Principally, The Mov Acts As A Sponge That Absorbs Short Duration Electrical Voltage Surges. A Typical Surge That The Mov Application Is Intended To Absorb Is Lightning, Which Is Characterized By A High Voltage And Potentially High Current Flow, But With A Short Time Duration. When The Energy Absorbing Capability Is Exceeded, The Mov Fails Catastrophically, Damaging Itself And Its Surroundings. The Amount Of Energy Which A Given Mov Can Absorb Without Exploding In A Flaming Fire Depends Upon The Voltage, Current. And Time Duration Imposed Upon It, And Also The History Of Prior Energy. This Article Describes The Mov And Explains How And Why It May Fail And Cause Subsequent Damage.